What a girl wants: A mixed-methods study of gender differences in the barriers to and enablers of riding a bike in Australia. (April 2023) - Pearson, Lauren; Reeder, Sandy; Gabbe, Belinda; Beck, Ben
Highlights: Women and men experience the same barriers to riding a bike, however women experience additional barriers related to their gender. Women have specific concerns about riding on the road alongside motor vehicle traffic and the associated risks, and experience confidence-related barriers to participation. There are opportunities to reduce the gendered inequities in bike riding outside of infrastructural changes. Abstract: Background: There is substantial potential to improve low rates of bike riding participation in Australian women. Understanding of the barriers to and enablers of riding a bike is essential for planning of urban environments and development of interventions to promote accessible active transport. It is well established that there are differences in the needs and experiences of people of different genders in urban environments, however our understanding of the needs of women who are not yet riding a bike are limited. We aimed to quantify perceived barriers and enablers to riding a bike for transport between women and men, and to explore reasoning behind these. Methods: Using a mixed methods sequential explanatory design, we purposively sampled people by age, gender and area of residence in Greater Melbourne, Australia. The sample participated in an online survey of barriers to and enablers of riding a bike. Participants who completed the online survey indicated if they were interested in participating in further qualitative research which aimed to gain a deeper understanding of their attitudes toward, barriers to and enablers of riding a bike. A total of 40 semi-structured interviews were conducted with 20 women and 20 men who were categorised as Interested but Concerned in bike riding. Results: Of the 912 surveys collected, 717 were completed and included in analyses. Significant differences were identified in the barriers and enablers reported between women and men, where more women reported concerns regarding riding on the road. In interviews, more women reported issues relating to a lack of confidence and concern about their safety riding a bike around motor vehicle traffic compared to men. Conclusions: Women have specific concerns about riding on the road alongside motor vehicle traffic and the associated risks, and a lack of confidence in their ability and knowledge of bike riding and bikes themselves. It is imperative that women's perspectives and needs are considered in the planning and promotion of bike riding globally to prevent and tackle gendered inequities.